Thermal annealing-induced electric dipole relaxation in natural alexandrite - Scalvi, RMF; Li, M. S.; Scalvi, LVA (Springer, 2005)
Electrical properties of natural alexandrite (BeAl2O4:Cr3+) are investigated by the thermally stimulated depolarization current (TSDC) technique. Samples are submitted to consecutive annealing processes and TSDC is carried out after each annealing, yielding bands with different parameters. These bands are fitted by a continuous distribution of relaxation parameters: activation energy and pre-exponential factor of the Arrhenius equation. It has been observed that annealing influences the dipole relaxation behavior, since it promotes a modification of Fe3+ and C3+ impurity distributions on sites of distinct symmetry: Al-1 and Al-2. In order to have a reference for comparison, TSDC is also carried out on a synthetic alexandrite sample, where the only impurity present is Cr3+ ion.
Keywords: alexandrite; electrical dipoles; annealing; depolarization current